Evaluation of the effects of and earliest response rate to anti-D treatment in children with chronic idiopathic thrombocytopenic purpura: a pilot study - Yetgin, Sevgi; Aytaç, Selin; Olcay, Lale; Tunç, Bahattin; Ozbek, Namik; Aydinok, Yeşim (The Turkish Journal of Pediatrics, 2010)
In this pilot study, 30 (14 male, 16 female; median age: 8 years, range: 2-18) chronic non-splenectomized idiopathic thrombocytopenic purpura (ITP) patients with Rh+ blood group and their 49 attacks were evaluated after intravenous (i.v.) anti-D (WinRho SDF, Cangene Corporation, Winnipeg, MB, Canada) treatment at a dose of 50 microg/kg x 3 days (n = 21 cases; 35 attacks) or a single dose of 75 microg/kg (n = 9 cases; 14 attacks) to define the hemostatic dose of anti-D. Five of 30 patients (22/49 attacks) were resistant to steroid, intravenous immunoglobulin (IVIG) and vincristine treatment. Hemoglobin (Hb), white blood cells (WBC), platelets (plt) and reticulocytes (ret) were evaluated before and after treatment during the follow-up in sequences on the 1st, 7th, 14th and 21st days after anti-D treatment if the patients had no symptom. All patients, even the resistant ones, experienced an increase in plt count to provide protection from bleeding (> or = 20 x 10(9)/L in patients with symptoms, > or = 10 x 10(9)/L in patients without symptoms). The plt responses of one resistant and five non-resistant patients treated with a single 75 microg/kg dose of i.v. anti-D in 8 attacks were monitored at the 2nd, 4th, 8th, 24th and 48th hours of the treatment. A protective plt level was attained within 2 hours in 6 attacks of five non-resistant cases and in 24 hours in the remaining 2 attacks of one resistant case. This pilot study suggests that anti-D treatment in ITP patients is effective and can increase plt to a level adequate enough to protect from hemorrhage within 2 hours, when given in a 75 microg/kg dose. A few adverse events (i.e. chills, hemolysis and hemoglobinuria) resolved without intervention.